Pengembangan produk baru dan siklus hidup produk di era modern - Agustina, Nurlaila Tria (Maliki Interdisciplinary Journal, 2025)
Product development is the process of changes made to existing products there is also a process of searching for innovation to add value to old goods. Meanwhile, the Product Life Cycle is an important concept in marketing because it provides a deep understanding of the dynamics competitor products. The purpose of this writing is to find out marketing strategies in developing new products, knowing the stages in the product life cycle strategy and know how to maintain the existence of new products. Data collection via books, journals, internet, and various other relevant information. Research result shows the importance of new product development and the product life cycle in the modern era It's all digital. Business actors are expected to be able to implement it product development strategy and product life cycle so that the product continues to exist in the market.